Exploring Fourth Grade Students’ Computational Thinking Skills in Mathematics Learning on Number Concepts - Suryaningsih, Tri; Rahayu, Wardani; Nurjannah (International Conference on Elementary Education, 2025)
This study aims to analyze the Computational Thinking (CT) skills of grade IV students in mathematics learning with number materials. Based on the CT skill test conducted on 37 students at SDN Sepanjang Jaya III, the results showed that students' ability in the indicators of decomposition (53.12%) and pattern recognition (54.68%) was still in the poor category, which indicated the difficulty of students in breaking down problems into simpler parts and recognizing patterns in numbers. Meanwhile, the indicators of abstraction (60.41%) and algorithmic thinking (77.34%) showed better achievements, although still in the sufficient category. These results reveal that students have begun to be able to sift through relevant information and follow problem-solving steps systematically, but still struggle in developing algorithms for more complex problems. This study suggests that mathematics learning in elementary school needs to place more emphasis on pattern exploration, problem-based learning, and unplugged activities to strengthen students' CT skills, especially in the aspects of decomposition and pattern recognition, as well as to encourage the development of logical and algorithmic thinking skills in a more in-depth manner.